Does Delivery Format Make a Difference in Learning About Global and Cultural Understanding?. Issue 2 (2nd April 2016) - Rawls, Janita; Hammons, Stacy A.
ABSTRACT: This study assessed a learning outcome for nontraditional seniors who were in accelerated degree programs in both online and on-site formats. Using items from the National Survey of Student Engagement, researchers explored engagement with global understanding and cultural awareness. A quantitative, single-case analysis method was used to determine significance with the items. Results indicated 50% of the items were significant, and for all of the significant items, means were higher for the on-site senior group. Implications are explored, including pedagogical ideas for online programs in teaching global and cultural themes.